Effect of Slope and Runoff Trends on the Hydrological Response of River Kaduna - Garba, Haruna; Abubakar, Zuwairat (ABUAD Journal of Engineering Research and Development (AJERD), 2023)
A monotonic upward/downward trends of hydrological variables was used to test the null hypothesis that slope and runoff trends have a significant impact on land use and land. The Mann-Kendall (M-K) and P- values statistical measurement were used to validate the null hypothesis against the observed data Relationships between gradients and climatic parameters for the hydrological response of Kaduna River was developed using geographic information tools (GIS). GIS maps of runoff, Digital Elevation Model (DEM), Land Use and Land were established Mann-Kendall (M-K) trend analysis was used to identify trends in climate parameters. The data used are precipitation, evapotranspiration, runoff, and temperature over a 30-year period from 1992 to 2021 obtained from the Kaduna State Water Authority and the Nigerian Meteorological Service. Results of the trend analysis of annual runoff and rainfall indicates the same M-K and P-values of 0.094 and 0.475which are all greeter than 0.05 significant level but the magnitude of Seen slope for rainfall and runoff are 5.130 and 0.016 demonstrating that rainfall is the major driving variable foe runoff generation. The annual evapotranspiration has M-K and P-values of 0.126 and 0.335 while the values for average annual temperature are 0.138 and 0.292. Land use in parts of the study area exhibits unstable ecosystems and vulnerable hilly terrain, suggesting that seasonal runoff and corresponding hydrological responses of rivers are dominated by changes in precipitation.